Supramolecular Surface Chemistry: Substrate-Independent, Phosphate-Driven Growth of Polyamine-Based Multifunctional Thin Films - Marmisolle, Waldemar A.; Irigoyen, Joseba; Gregurec, Danijela; Moya, Sergio; Azzaroni, Omar (Advanced Functional Materials, 2015)
The ability to engineer surfaces at the supramolecular level by controlled integration of specific chemical units through substrate-independent methodologies represents one of the new paradigms of contemporary materials science. Here, a method is reported to form multifunctional supramolecular coatings through simple dip-coating of substrates in an aqueous solution of polyamine in the presence of phosphate anions. The chemical richness and versatility of polyamines are exploited as phosphate receptors to form thin functional films on a broad variety of substrates, ranging from metal to carbonaceous surfaces. It is shown that the simple derivatization of pendant amino groups of polyallylamine precursors with different chemical groups can endow films with predefined responsiveness or multiple functions - this translates into one-pot and one-step preparation of substrate-adherent films displaying built-in functions. It is believed that the flexibility, speed, and versatility with which this method provides such robust functional films make it very attractive for preparing samples of fundamental and technological interest.
CRIS-Team Scopus Importer:2020-10-13
Keywords: bioinspired materials; functional thin films; self-assembly; supramolecular materials; surface chemistry